Akuntansi dalam Perspektif Maqashid Syariah - Khusnudin Khusnudin (Universitas Jember, 2017)
Islam as a way of life for Muslims explains comprehensively about worship and muamalah, including in non-cash economic transactions. Various verses in the Koran provide guidance to document non-cash transactions. Honesty, accountability and piety are needed in the recording process. How is the implementation of sharia maqasid in accounting to be important to know. Qualitative research through literature study by studying the normative aspects of the verses of the Koran and the hadith, as well as analyzing through the maqashid sharia approach. Accounting as a complement (tahsiniyat) can turn into a need (hajiyat) at the maqashid level. Sharia orders to record non-cash transactions become a necessity (dharuriyat) to protect property ownership. Keywords: Accounting, Transactions, Maqashid Sharia